A bird's eye view on Kantakari Avaleha: A polyherbal Ayurveda formulation for bronchial asthma - Sagar Mahendrabhai Bhinde; Sonam Sagar Bhinde; Virendra K Kori; Kalpna S Patel (Wolters Kluwer Medknow Publications, 2022)
Avaleha (linctus) is a unique dosage form of Ayurveda pharmaceutics, which is frequently used in various disorders and especially in respiratory disorders. Kantakari Avaleha (KA) is one such formulation being used extensively for Shwasa (asthma) and Kasa (cough) along with its classical use in various other disorders too. Because of its demand in clinical settings, many pharmaceutical companies are also preparing this, and hence freely available in market. This review was carried out to get thorough idea related to its composition, method of preparation, and therapeutic uses along with its pharmaceutical standards. For this review, classical and compiled texts having subject of Ayurveda pharmaceutics were screened from Central Library of Institute of Teaching and Research in Ayurveda, Jamnagar. Out of total 15 texts screened, 7 texts had mentioned KA, and hence reviewed for its ingredients, dose, Anupana, and therapeutic uses. Synonyms, Rasapanchaka (Ayurveda principles of drug action), and Dosha Karma (therapeutic action) of ingredients were compiled from Bhavaprakasha Nighantu. Pharmaceutical parameters of KA were compiled from original research articles from peer-reviewed journals through Google Scholar, PubMed, ResearchGate, and J-Gate portal. After review, it was found that Acharya Sharangdhara (12th Century) had described this formulation for the first time. There are four variations available in formulation composition. Milk or water should be the Anupana for this drug as per Ayurvedic Formulary of India and Pharmacopoeia of India (API). Almost all references have recommended its use in Shwasa and Kasa, along with Arati (distress), Shula (colicky pain), Gulma (a type of lump), Hikka (hiccup), and Hradroga (heart disease) mentioned in one and the other classics. Maximum ingredients of this formulation possess hot potency (12 out of 18 drugs) and pungent biotransformation property (11 out of 18 drugs). As per available original research works, two laboratory samples and one market sample of KA had fulfilled almost all analytical parameters, mentioned in API. The current review work may be helpful as stepping stone for various researches on KA such as network pharmacology, in silico, pharmacology, and longitudinal cross-sectional, clinical study.